1992
DOI: 10.1002/eji.1830220721
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecules of the immunoglobulin supergene family as tissue‐specific autoantigens: induction of experimental allergic neuritis (EAN) by PO protein‐specific T cell lines

Abstract: The P0 glycoprotein is a homophilic cell adhesion molecule of the immunoglobulin supergene family which is responsible for maintaining the structure of compact internodal myelin in the peripheral nervous system (PNS). Utilizing a panel of synthetic P0 peptides two distinct T cell epitopes have been identified that can induce T cell-mediated experimental autoimmune neuritis (EAN) in the Lewis rat. One T cell epitope (amino acid residues 56-71), is located within the extracellular, immunoglobulin-like domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 30 publications
3
45
1
1
Order By: Relevance
“…Our results seem contradictory to recent data showing that P0-reactive T cells are eliminated in a gene-dosage dependent manner (10). However, those results were obtained using another peptide, P0 180 -199, which was initially described as an immunodominant peptide in Lewis rats (5). Our mapping experiments of the immune response to P0 on BL/6 background prompted us to use the immunodominant determinant of P0 (P0 41-60), which may behave differently compared with the P0 180 -199.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results seem contradictory to recent data showing that P0-reactive T cells are eliminated in a gene-dosage dependent manner (10). However, those results were obtained using another peptide, P0 180 -199, which was initially described as an immunodominant peptide in Lewis rats (5). Our mapping experiments of the immune response to P0 on BL/6 background prompted us to use the immunodominant determinant of P0 (P0 41-60), which may behave differently compared with the P0 180 -199.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in these P0-deficient mice revealed the potential of P0 to act as an immune target (2). Moreover, Ab responses to P0 have been detected in patients' sera with chronic polyneuritis (3) and immunization with P0 peptides and adoptive transfer of peptide-specific T cells induce experimental autoimmune neuritis in susceptible animals (4,5).…”
mentioning
confidence: 99%
“…Why P 0 appears to be a main immunogenic component in P 0 ϩ/Ϫ mice is presently not known. In experimental autoimmune neuritis (EAN) in rat, P 2 is a much stronger neuritogen than P 0 (Linington et al, 1992), but there might be differences among species. On the other hand, even in heterozygous mutants, P 0 is still the most abundant peripheral myelin protein (Giese et al, 1992) which could explain a substantial role of P 0 as an immunogenic component.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of T cell reactivity in GBS, all these peptides were shown to cause reactivity [23]. P2 57-81 [24], P0 56-71 and P0 180-199 [25] induce experimental allergic polyradiculoneuritis (EAN), which is the animal model of GBS, in rats. P0 56-71 is located in the extracellular immunoglobulin-like domain of P0, while P0 180-199 and P0 194-208 are located in the cytoplasmic carboxyterminal domain of the protein.…”
Section: Preparation Of Pbmcmentioning
confidence: 99%